Railroaded: The Creation of Immigration Facilities in Halifax, 1889–1928 - Schwinghamer, Steven (Journal of the Royal Nova Scotia Historical Society, 2023)
A series of buildings were used for Canadian immigration operations at Pier 2 in Halifax, Nova Scotia, from the late 1800s through the early 1900s. The histories of those facilities show that transportation companies exerted significant control over Canadian immigration and passenger facilities in Halifax. The planning, construction, and operation of immigration sheds at Pier 2 did not hinge on decisions by the federal immigration branch; in fact, the facilities were often built and operated in ways that ran counter to both the wishes and the requirements of immigration. Instead, the immigration buildings proceeded from the pressures of a mix of private and public organizations, including railways and steamship lines, government departments and municipal business representatives. At Halifax, like other Canadian immigration ports of entry, the particularities of place resulted in unique and distinct sites, structures, practices, and experiences of immigration.